PENGARUH KEPEMIMPINAN, MOTIVASI, PELATIHAN, DAN DISIPLIN, TERHADAP KINERJA (Survei pada Perawat RSUD Dr. Harjono S Kabupaten Ponorogo) - Etikawati, Dina; Suddin, Alwi; Sutarno, Sutarno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
The purpose of this study was to analyze the significance effect of leadership, motivation, training, discipline tothe performance of nursing at Regional General Hospital (RSUD) Dr. Harjono S Ponorogo Regency.Data collection in the form of questionnaire answers as primary data and documentation as secondary data. The number of research samples is 100 employees with sampling methods using saturated sampling. The data analysis method used is validity and reliability test, classic assumption test, hypothesis test, F test, and test coefficient of determination.The results of regression calculations indicate that the motivation and discipline have a significant effect on job satisfaction. This is indicated by the significant probability value of each variable < 0,05. While the leadership and the training does not have a significant effect on the performance of financial staff at the RSUD Dr. Harjono S Ponorogo Regency. This is indicated by a significant probability value > 0,05.